2019
DOI: 10.5463/dcid.v29i4.785
|View full text |Cite
|
Sign up to set email alerts
|

Accessibility of Public Buildings in Khulna, Bangladesh, for Wheelchair Users

Abstract: Purpose: Physical accessibility is one of the fundamental rights of wheelchair users in order to ensure their integration into society. After Bangladesh ratified the UN Convention on the Rights of Persons with Disabilities (CRPD) on November 30, 2007, there has been a paradigm shift in the government’s approach to ensure the welfare and rights of persons with disabilities through legislative and policy actions. This study assesses how accommodative the public buildings are for wheelchair users in Khulna, Bangl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…Height differences, limited widths, and excessive slope gradients are common factors for the observed incongruence. Those outcomes agree with international studies, which have found that the actual design of several physical elements does not harmonise with accessibility standards [92][93][94]. A possible explanation of this might be that a substantial portion of public spaces had been constructed before accessibility standards were introduced.…”
Section: Discussionsupporting
confidence: 86%
“…Height differences, limited widths, and excessive slope gradients are common factors for the observed incongruence. Those outcomes agree with international studies, which have found that the actual design of several physical elements does not harmonise with accessibility standards [92][93][94]. A possible explanation of this might be that a substantial portion of public spaces had been constructed before accessibility standards were introduced.…”
Section: Discussionsupporting
confidence: 86%
“…These are listed as items 2, 8, 17, 22, 26 and 28. Ahmed et al (2014) and Farzana (2019) indicated wheelchair resting place, designed parking spots, furnitures and signages to have minimal attainment. Similarly, Muzemil (2018) observed space, services and other building features to hinder full participation for PWD.…”
Section: Comparative Studymentioning
confidence: 99%
“…Despite substantial advances in numerous sectors, persons with disabilities in Bangladesh remain one of the most marginalized groups. They continue to face discrimination, are socially excluded, and lack access to essential social services in Bangladesh (Farzana, 2018). However, they cannot be kept out of society or denied their rights to participate in all parts of the physical, cultural, social, and economic environment, as well as education, health, and informal communication (Machado & de Oliveira, 2021).…”
Section: Introductionmentioning
confidence: 99%